Застосування кластеризації на основі машинного навчання для вдосконалення управління популяціями бездомних тварин - Бєгунова, В. Д. (ХНУРЕ, 2024)
This work is devoted to developing methods for managing populations of stray animals, particularly through analyzing the duration of their stay in shelters. The primary focus is on creating a technological solution that adapts to the unique characteristics of each animal and provides flexibility in response to changing conditions and data limitations. The main goal is to identify the specific needs and behavioral characteristics of animals based on their time spent in shelters, in order to optimize care processes, reduce the time it takes to find new homes for animals, and improve resource allocation between shelters. The application of clustering algorithms, such as k-means, will allow grouping animals with similar behavioral characteristics and needs based on their shelter stay time, thereby facilitating the development of targeted adaptation programs and accelerating the process of finding new owners
Keywords: управління популяціями тварин; тварина